Simko’s Movements in Kurdistan Iran and the Impact of Colonial Powers: Russia, Britain until 1930 - إدريس صالح حسن عبدالرحمن (Al-Adab Journal, 2018)
Simko’s uprising was one of the prominent movements in Iran’s contemporary history, through which Simko sought to create an independent Kurdish entity in northern Iran, as he played the role of being opponent against the authoritarian central policy of Iran and his role became quite clear during the world war I and postwar. He was well known among Russian, British, Iraqi, Iranian and Turkish diplomatic offices. He was considered a typical character for clan leader and rebel, rejecting the difficult circumstances that Kurds burdened with. The study has been divided into an introduction, with five sections and a conclusion. The first section addressed the region of Kurdistan in Iran and its strategic importance at local, regional and international levels. The second section is devoted to personal profile of Simko, his tribal affiliation and his revolutionary activities. The third section studies the impact of the colonial powers (Russia and Britain) on Simko’s expectations in the region. Fourth section approaches simko’s movements and their effects on the local and regional perspectives and the opposite direction. The last section is dedicated to illustrate the role played by some (internal and external) parties to bring smko’s movements to an end and then assassinate him in July 1930. This research paper based on a number of relevant sources which belong to different trends that primarily include unpublished documents including documents of British Foreign Office and documents of the Ministry of colonies. They involve the best information related to followed British plans and procedures. Additionally, the paper relied on the documents of Iraqi Royal Court, which were archived in Iraqi National Library and Archives in Baghdad, as they were of greater significance in this paper. The research draws upon some Arabic anf other foreign newspapers that have accompanied and recorded the situations and other events around the world. Dissertations and other references in Arabic with translated resources were the basic data which has been adopted by the researcher in this paper.